ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE AND CORPORATE VALUE: UNPACKING THE MODERATING EFFECT OF COMPANY SIZE - Dendi Mulyana; Aristanti Widyaningsih; Rozmita Dewi Yuniarti Rozali (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: This study endeavours to analyse the effect of environmental, social, and governance (ESG) performance on corporate value and determines whether company size can affect this outcome.